PENGARUH PENGGUNAAN METODE PEER TUTORING TERHADAP MOTIVASI DAN PRESTASI BELAJAR MATEMATIKA PADA SISWA SEKOLAH DASAR - , RANNI RAHMAYANTHI.Z.,S.Pd, Supra Wimbarti, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The aim of this study is to find out the impact of peer tutoring method toward motivation and mathematics achievement on student in elementary school. The subject research is 66 students in fifth grade SD Negeri 3 Perum Way Kandis Tanjung Seneng Bandar Lampung. One group was experimental group which was given the teaching with the peer tutoring method to learn math, while other group was as control group which was given the teaching with conventional method. Result of examination of hypothesis indicated that peer tutoring method give significant and positive influence toward motivation and mathematics achievement on student in elementary school. It was shown by the t value for the mathematics motivation is t = 2,520 (p = 0,014) while for the mathematics achievement t = 3,572 (p = 0,001).